Volpe's neurology of the newborn - Volpe, Joseph J; Inder, Terrie E; Darras, Basil T; De Vries, L. S; Du Plessis, Adré J; Neil, Jeffrey J; Perlman, Jeffrey M (Elsevier, 2018)
A clear, engaging writing style, hundreds of full-color images, and new information throughout make Volpe’s Neurology of the Newborn, 6th Edition, an indispensable resource for those who provide care for neonates with neurological conditions. World authority Dr. Joseph Volpe, along with Dr. Terrie E. Inder and other distinguished editors, continue the unparalleled clarity and guidance you’ve come to expect from the leading reference in the field - keeping you up to date with today’s latest advances in diagnosis and management, as well as the many scientific and technological advances that are revolutionizing neonatal neurology.
Keywords: Nervous System Diseases; nemoci nervového systému; Infant, Newborn; Infant; kojenec; novorozenec; perinatologie a neonatologie; neurologie